Ischaemic heart disease in patients with diabetes mellitus and critical lower limb ischemia - Konstantin Vladimirovich Melkozerov; Victor Yur'evich Kalashnikov; Sergey Anatol'evich Terekhin; Olga Nikolaevna Bondarenko (Сахарный диабет)
Aims. To assess prevalence of ischemic heart disease (IHD) and clinical features of asymptomatic IHD in patients with diabetes mellitus(DM) and critical lower limb ischemia (LLI).Materials and Methods. We examined 118 patients with DM, who underwent hospitalization for critical LLI. Besides routinecardiologic examination, all patients were subject to color duplex ultrasonography of lower limbs and CT contrast angiography. Patientswith proper indications underwent coronary angiography. Statistical data was processed with SPSS v17.0.0. software package. Results. We have found 58.5% of patients with DM and critical LLI to suffer from IHD - and approximately 40% to have myocardialinfarction in their medical history. According to acquired coronary angiograms, 89% of asymptomatic cases were characterized byhemodynamically significant stenosis, while 68.7% of them had either three arteries affected or left main coronary artery lesions. Conclusion. Patients with DM and critical LLI require thorough examination, as subclinical IHD may be masked in them by lowerlimb angiopathy.